The Effect of Students' Conceptual Error-Based Learning Tools on the TPACK Ability of Prospective Teachers - Dwijayanti, Ida; Andri Nugroho, Aryo; Esti Utami, Rizky (KnE Social Sciences, 2022)
This study aimed to determine the effect of learning tools based on the analysis of students’ conceptual errors on TPACK abilities. This study uses an experimental method involving 105 samples in extracting the initial TPACK data owned by students studying to be teachers and their teachers. In the final data collection, 2 students carried out learning using a device that had been designed based on the possibility of student errors in the trial class, and 2 teachers taught conventionally in the control class. The data was taken by observing the TPACK indicator’s achievement for students and teachers. The study results show that the content knowledge capabilities of prospective teachers have a better opportunity to present more actual problems and provide opportunities for students to develop higher-order thinking skills. In this case, the students introduced the concept of algebra (variables, coefficients, constants and real number operations) in the problem of managing pocket money, while the teacher gave the problem of the number of balls in a cardboard box. The implication is that the readiness of prospective teachers to teach will be better. Keywords: conceptual error-based learning, TPACK ability